TSG101 promotes the proliferation, migration and invasion of hepatocellular carcinoma cells by regulating the PEG10 - Liu, Zhiyi (J Cell Mol Med, 2018)
The tumour susceptibility gene 101 (TSG101) is reported to play important roles in the development and progression of several human cancers. However, its potential roles and underlined mechanisms in human hepatocellular carcinoma (HCC) are still needed to be further clarified. In the present study, we reported that knock down of TSG101 suppressed the proliferation, migration and invasion of HCC cells, while overexpression of TSG101 facilitated them. Molecularly, the results revealed that knock down of TSG101 significantly decreased the cell cycle related regulatory factor p53 and p21. In another point, knock down of TSG101 also obviously decreased the level of metallopeptidase inhibitor TIMP1 (Tissue inhibitors of metalloproteinases 1), which results in inhibition of MMP2, MMP7 and MMP9. In contrast, overexpression of TSG101 had opposite effects. The iTRAQ proteomics analysis identified that oncogenic protein PEG10 (Paternally expressed gene 10) might be a potential downstream target of TSG101. Further investigation showed that TSG101 interacted with PEG10 and protected it from proteasomal degradation thereby regulating the expression of p53, p21 and MMPs. Finally, we found that both TSG101 and PEG10 proteins are up‐regulated and presented a direct correlation in HCC patients. In conclusion, these results suggest that TSG101 is up‐regulated in human HCC patients, which may accelerate the proliferation, migration and invasion of HCC cells through regulating PEG10.